Design, Synthesis, Antibacterial Evaluation and Docking Study of Novel 2‐Hydroxy‐3‐(nitroimidazolyl)‐propyl‐derived Quinolone. (16th August 2014) - Li, Qing; Xing, Junhao; Cheng, Haibo; Wang, Hui; Wang, Jing; Wang, Shuai; Zhou, Jinpei; Zhang, Huibin
<x xml:space="preserve">Abstract</x> A novel series of 2‐hydroxy‐3‐(nitroimidazolyl)‐propyl‐derived quinolones 6a–o were synthesized and evaluated for their in vitro antibacterial activity. Most of the target compounds exhibited potent activity against Gram‐positive strains. Among them, moxifloxacin analog 6n displayed the most potent activity against Gram‐positive strains including S. epidermidis (MIC = 0.06 μg/mL), MSSE (MIC = 0.125 μg/mL), MRSE (MIC = 0.03 μg/mL), S. aureus (MIC = 0.125 μg/mL), MSSA (MIC = 0.125 μg/mL), (MIC = 2 μg/mL). Its activity against MRSA was eightfold more potent than reference drug gatifloxacin. Finally, docking study of the target compound 6n revealed that the binding model of quinolone nucleus was similar to that of gatifloxacin and the 2‐hydroxy‐3‐(nitroimidazolyl)‐propyl group formed two additional hydrogen bonds.